A inserção de práticas integrativas e complementares no ensino superior e os desafios enfrentados pela educação em ciências da saúde - Meza, Sheila Karina Lüders (2025)
Integrative and Complementary Health Practices (PICS) consist of therapeutic resources recognized by the World Health Organization (WHO). They offer a humanized and self-awareness-based approach, integrated with nature, aiming to promote balance between body, mind, and spirit through simple resources. To ensure effective and high-quality implementation, it is essential to incorporate them into the education of healthcare professionals at the higher education level, ensuring proper availability to the population. However, integrating these practices into higher education is a highly complex topic that brings different epistemological paradigms into discussion. This study aims to understand the challenges of incorporating PICS into undergraduate programs in the field of human health sciences at state public higher education institutions in Paraná, Brazil. Seeking clarification, identifying the availability and profile of courses that cover at least one of the techniques recognized by Brazil’s National Policy on Integrative and Complementary Practices (PNPIC) was included as secondary objects. Additionally, we seek to understand how these contents are selected, with what objectives, and to analyze the challenges surrounding this process based on the Epistemology of Complexity. Furthermore, we investigated whether professional councils of the involved categories have specific regulations that recognize and regulate these specialties as legally established professional attributions. The methodology used in the investigative process was descriptive documentary research, and data analysis was conducted using Bardin’s Content Analysis method. Based on the evaluation of data from questionnaires, scientific findings, and documents, as well as the analysis of this information, insights and proposals regarding the complexity of the phenomenon are developed, fostering discussions on the limits and potentialities of integrating PICS into health sciences education. As an outcome of this debate, we identified inconsistencies between the PNPIC and the National Curriculum Guidelines (DCNs) for higher education in health sciences, particularly regarding the inclusion of PICS in Pedagogical Political Projects (PPPs), as well as discrepancies in the professional regulations issued by the professional councils. Among the evaluated programs, Pharmacy was the only one that incorporated PICS into both its DCNs and PPPs, albeit incipiently. Registration data provided by the Regional Pharmacy Council of Paraná (CRF-PR) in November 2023 highlights the profile of pharmacists in Paraná working with PICS. The specialty with the highest number of legally practicing professionals in the state was Homeopathy, followed by Acupuncture and Ozone Therapy. In the other programs assessed in this research, there was no evidence of a structured approach to PICS, except for the Physical Therapy program at Universidade Estadual do Oeste do Paraná (Unioeste) – Cascavel campus, which is the only state university physical therapy program in Paraná to include a course addressing PNPIC content, albeit superficially. Given this context, the aim of this investigation is to contribute to a more humanized professional education in healthcare by establishing a dialogue xiv with scientific culture, expanding critical perspectives on the process, and, in doing so, aligning with Brazil’s health guidelines.